Prescribing patterns of systemic antifungal medications in Indian patients with invasive fungal infections: a multicenter retrospective study - Patel, Lav; Sharma, Shreekant; Bunger, Deepak (International Journal Of Community Medicine And Public Health, 2022)
Background: Objectives of the study was to describe the utilization pattern of systemic antifungal agents in Indian patients with invasive fungal infections (IFIs). Methods: This real-world, multicenter (127 centers), retrospective analysis included data of patients receiving systemic antifungal medications at various centers across India. The study data was collected between April 2021 and March 2022. Results: Data of a total of 323 patients was analyzed. The mean age of patients was 54±13.52 years. There was male preponderance seen in this study (72.4%). Diabetes was the most common comorbidity (36.8%) followed by concomitant diabetes and hypertension (31.9%), hypertension (9.6%) and hematological malignancies (9.6%). The most common indication occurring in >10% of the patients and for whom systemic antifungals were used included pulmonary mucormycosis (33.1%) followed by invasive candidiasis (16.1%), sepsis (13.3%) and fungal pneumonia (11.8%). In total 323 patients, the most common antifungal drug prescribed was posaconazole (38.6%) followed by anidulafungin (32.8%), caspofungin (10.5%), fluconazole (9.3%) and micafungin (8.7%). Posaconazole was most commonly used for pulmonary mucormycosis (84.8%), fluconazole for sepsis (33.3%), caspofungin for fungal pneumonia (23.5%) and anidulafungin (33.1%), and micafungin (39.3%) for invasive candidiasis. Conclusions: This study provides real-world evidence on the demographics of Indian patients with IFIs and utilization pattern of systemic antifungals by health care physicians in clinical practice.